2016
DOI: 10.17235/reed.2016.3934/2015
|View full text |Cite
|
Sign up to set email alerts
|

Glycogenic hepatopathy in young adults: a case series

Abstract: Glycogenic hepatopathy is a rare and underecognized complication in long-standing poorly controlled type 1 diabetes mellitus patients. This is a distinct entity from other causes of hepatomegaly and elevated liver enzymes in diabetics, such as nonalcoholic fatty liver disease. Glycogenic hepatopathy is characterized by the combination of poorly controlled diabetes, acute liver injury with marked elevation in serum aminotransferases, and the characteristic histological features on liver biopsy. It is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Although a few reported cases had normal liver sizes on imaging studies, hepatomegaly was observed in more than 90% of the reported cases, with varying degrees of elevation in transaminases and rarely an elevation in alkaline phosphatase (ALP) level. Excessive glycogen with swollen hepatocytes eventually could cause sinusoidal compression and subsequent ascites[ 34 ]; therefore, ascites can also be a part of the clinical presentation, albeit rarely[ 34 , 44 ]. Physical examination of patients with GH generally exhibits tender hepatomegaly without splenomegaly.…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…Although a few reported cases had normal liver sizes on imaging studies, hepatomegaly was observed in more than 90% of the reported cases, with varying degrees of elevation in transaminases and rarely an elevation in alkaline phosphatase (ALP) level. Excessive glycogen with swollen hepatocytes eventually could cause sinusoidal compression and subsequent ascites[ 34 ]; therefore, ascites can also be a part of the clinical presentation, albeit rarely[ 34 , 44 ]. Physical examination of patients with GH generally exhibits tender hepatomegaly without splenomegaly.…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…GH is underrecognized and often confused with fatty liver disease and nonalcoholic steatohepatitis, which is more common in type 2 diabetes. e exact incidence and prevalence of the disease are unknown [1][2][3][4][5][7][8][9][10][11]. Classically it is seen in longstanding, poorly controlled, type 1 diabetes (98% of cases) with a mean duration of 10.5 years and a mean HbA1c of 11.8 [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…e mechanism of ascites remains unclear [1]. Other laboratory abnormalities in patients with GH include a high amylase and/or lipase in patients with no clinical or radiographic evidence of acute pancreatitis [11]. e underlying mechanism of this is also unknown [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After GH diagnosis, the treatment should aim the intense glycemic control as this is considered the backbone of its management 15 34 44. However, resolution of GH has also been described after minimal glucose control 34 45.…”
Section: Discussionmentioning
confidence: 99%